The Cultivation of Cultural Intelligence in the EFL Classroom: An Interpretive Meta-Synthesis Study - EL Harras, Loubna; Ennam, Abdelghanie (International Journal of Language and Literary Studies, 2025)
In our 21st century and in the age of rapid globalization there is a constant change in both learning and teaching processes. Nowadays, learning English does not merely involve learning the four skills beside of grammar since learning English exceeds that to what is pragmatic as well. That is, to effectively interact, relate to people with distinct cultures, act appropriately and be competently able to communicate despite cultural differences and ethnic backgrounds, fostering the cultural intelligence paradigm within our Moroccan EFL context is pivotal. Thus, cultural intelligence is one of the most current issues in language learning and teaching that requires nowadays much attention and focus from researchers, curriculum designers and teachers. Therefore, this study aims to highlight the importance of cultural intelligence within EFL classrooms as well as it investigates the ways that EFL teachers should wend to develop the cultural intelligence of their learners. Further, this research attempts to uncover key benefits of cultural intelligence on the learner on the basis of examining qualitative and quantitative studies. For this, a meta-synthesis research was adopted as a research design. 20 studies about cultural intelligence within EFL classrooms were included to meet the aim of the interpretive meta-synthesis research. Therefore, after reading, analyzing, and comparing different studies about boosting cultural intelligence within EFL context, it is confirmed that this cultural intelligence yields pivotal outcomes for the learners as developing intercultural competence, cultural awareness, communicative skills and cultural sensitivity. Also, its cultivation relies on many requirements such as incorporating the intercultural content, encouraging experiential learning and implementing useful assessment strategies.